Decline of the Corporate Community Network Dynamics of the Dutch Business Elite - Heemskerk, Eelke M. (Amsterdam University Press, 2007)
From its inception, big business in the western industrialised world has been organised in national business communities. Central elements of these business communities are corporate board interlocks that constitute the notorious 'Old Boys Network'. This corporate elite connects the centres of corporate governance. In recent times, these networks of the corporate elite show signs of decline. Heemskerk investigates how the decline of the old boys network in the Netherlands has affected Dutch capitalism. Combining formal network analysis with insights from interviews with key corporate elite members, he shows how during the last quarter of the 20th century the Dutch business community has disappeared. This is interpreted as a drift towards a liberal market economy. However, as the study shows, even in a liberal market economy corporate directors need social networks to communicate and coordinate their strategic decisions. Hence, the corporate elite shift its meeting network to private and informal circles. To order this book, mail to "mailto:orders@aup.nl">orders@aup.nl